A comparison of quadriplegic and hemiplegic cerebral palsy - Lagunju, Ike A.; Adedokun, Babatunde O. (Journal of Pediatric Neurology, 2008)
Cerebral palsy (CP) is one of the leading causes of childhood disability worldwide. Children in the developing world are disproportionately affected with majority of the cases resulting from preventable causes. Various topographic classes of CP have been described in literature, with varying degrees of functional impairments and neuro-cognitive dysfunction. We aimed to compare the characteristics of children with quadriplegic and hemiplegic CP. Two hundred and thirty six consecutive cases of CP, 186 with spastic quadriplegia and 50 with spastic hemiplegia seen over a period of 30 months were studied. Their demographic characteristics, functional and associated neuro-cognitive impairments were compared using the SPSS for windows software. The study showed relatively high proportions (20.3%) of post-neonatally acquired CP. Children with spastic quadriplegia were found to present at a relatively younger age than those with hemiplegia. Spastic hemiplegia was found to be associated with mild to moderate degrees of functional impairment (P < 0.001), and a significantly lower prevalence of hearing impairment (P < 0.001), speech defects (95% CI OR =1.50–7.19), mental retardation (0.026) and growth impairment (P < 0.001). Although epilepsy was a common associated deficit in quadriplegic CP, a higher prevalence was found in the hemiplegic group. We can conclude that hemiplegic CP is a less severe disease compared with quadriplegic CP. Post-neonatally acquired CP accounts for a significant proportion of CP in Nigeria, and majority are due to intracranial infections. Although, CP cannot be cured, prompt diagnosis of this condition and early identification of the associated deficits and institution of the necessary management will often improve the child's capabilities.
Keywords: Quadriplegia; hemiplegia; cerebral palsy